2014
DOI: 10.1515/bmt-2013-0088
|View full text |Cite
|
Sign up to set email alerts
|

Influence of superstructure geometry on the mechanical behavior of zirconia implant abutments: a finite element analysis

Abstract: To predict the clinical performance of zirconia abutments, it is crucial to examine the mechanical behavior of different dental implant-abutment connection configurations. The international standard protocol for dynamic fatigue tests of dental implants (ISO 14801) allows comparing these configurations using standardized superstructure geometries. However, from a mechanical point of view, the geometry of clinical crowns causes modified boundary conditions. The purpose of this finite element (FE) study was to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…However, cobalt–chromium crowns exhibit lower detail accuracy and higher shrinkage after casting than gold alloys [ 30 ]. The superstructure geometry and related surface peculiarities influenced the mechanical behavior of the various abutment–prosthesis (crown) connections [ 38 , 39 ]. A conical connection between abutment and crown was performed because in vivo studies revealed significantly lower bacterial counts in the peri-implant sulci and inside the connections in the internal hexagons of the external collar connection and conical connection groups [ 4 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, cobalt–chromium crowns exhibit lower detail accuracy and higher shrinkage after casting than gold alloys [ 30 ]. The superstructure geometry and related surface peculiarities influenced the mechanical behavior of the various abutment–prosthesis (crown) connections [ 38 , 39 ]. A conical connection between abutment and crown was performed because in vivo studies revealed significantly lower bacterial counts in the peri-implant sulci and inside the connections in the internal hexagons of the external collar connection and conical connection groups [ 4 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the key factors for long-term clinical success is correct planning of the substructure and superstructure materials that support the implant prosthesis. The properties of the material and spatial geometric configuration model of each component have a significant impact on the transference of functional loads and stress distribution in a bone–implant–prosthesis assembly [ 2 ]. In the oral environment, these components act in unison with each other, and thus the combination of the materials used is important.…”
Section: Introductionmentioning
confidence: 99%
“…This International Standard is most useful for comparing endosseous dental implants of different designs or sizes 18 , 19 . Several previous studies compared different implant designs applying this protocol in terms of stress and strain distribution, 20 , 21 torque evaluation, 13 , 22 and bending moment 23, 24, 25. By using the same protocol, comparing between different studies could be possible.…”
Section: Discussionmentioning
confidence: 99%